Information Risks with Internet of Things in Cultural Creative Industry - Ren Hsu, Der (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2018)
Internet of Things (IoT) is characterized by various technologies, which are in accord to the provisioning of innovative services in innumerable application domains. In cultural creative industry, Internet of things has been widely practiced now, and will still have many creative potential in art work applications. In this consequence, the satisfaction of risk management requirements plays a fundamental role. Unfortunately, there is little objective, scientific research focused on evaluating the risks of security issues that result from information exchange among Internet of Things. In this study, the Grey Relational Analysis (GRA) is employed to identify and evaluate the risks of IoT. This research finds that Privacy, Access Control, and Trust are the top three risk factors. Using IoT in cultural creative industry is a new inevitable business trend, it is an unavoidable responsibility to our society to govern and constitute a healthy environment for all the related users.